2021
DOI: 10.1016/j.jvscit.2021.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of partial resection in venous adventitial cystic disease

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Interestingly, a recent study reported no recurrence after 10-year follow-up even in a patient with partial resection of CAD cyst. 11 It seemed that minimally invasive and endovascular treatment for CAD were associated with a higher recurrence rate as compared with complete surgical evacuation and excision of the cyst. 12 Typically for a CAD small in size, transverse venous division with complete cyst wall removal and end-to-end venous re-anastomosis could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study reported no recurrence after 10-year follow-up even in a patient with partial resection of CAD cyst. 11 It seemed that minimally invasive and endovascular treatment for CAD were associated with a higher recurrence rate as compared with complete surgical evacuation and excision of the cyst. 12 Typically for a CAD small in size, transverse venous division with complete cyst wall removal and end-to-end venous re-anastomosis could be considered.…”
Section: Discussionmentioning
confidence: 99%